2016
DOI: 10.14336/ad.2016.0323
|View full text |Cite
|
Sign up to set email alerts
|

Brain Formaldehyde is Related to Water Intake behavior

Abstract: A promising strategy for the prevention of Alzheimer’s disease (AD) is the identification of age-related changes that place the brain at risk for the disease. Additionally, AD is associated with chronic dehydration, and one of the significant changes that are known to result in metabolic dysfunction is an increase in the endogenous formaldehyde (FA) level. Here, we demonstrate that the levels of uric formaldehyde in AD patients were markedly increased compared with normal controls. The brain formaldehyde level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
9
0
4
Order By: Relevance
“…The concentration of endogenous formaldehyde is positively correlated with the severity of cognitive impairments in Alzheimer’s disease (AD) patients [21], which is due to the metabolic imbalance between synthesis and degradation of formaldehyde [16,34]. The average pathological concentration of formaldehyde in the urine of AD patients is 13.70 ± 5.17 μM, i.e., the pathological urine formaldehyde concentration for AD is ˜1.4 times as much as the physiological concentration (9.61 ± 2.90 μM) in age-matched normal participants [24]. Accumulation of a pathological concentration of endogenous formaldehyde (15 μM) induced chronic damage to N2a cells [24,51], especially the impairment of neuronal processes and neurites, which may result from Tau hyperphosphorylation [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of endogenous formaldehyde is positively correlated with the severity of cognitive impairments in Alzheimer’s disease (AD) patients [21], which is due to the metabolic imbalance between synthesis and degradation of formaldehyde [16,34]. The average pathological concentration of formaldehyde in the urine of AD patients is 13.70 ± 5.17 μM, i.e., the pathological urine formaldehyde concentration for AD is ˜1.4 times as much as the physiological concentration (9.61 ± 2.90 μM) in age-matched normal participants [24]. Accumulation of a pathological concentration of endogenous formaldehyde (15 μM) induced chronic damage to N2a cells [24,51], especially the impairment of neuronal processes and neurites, which may result from Tau hyperphosphorylation [51].…”
Section: Discussionmentioning
confidence: 99%
“…The average pathological concentration of formaldehyde in the urine of AD patients is 13.70 ± 5.17 μM, i.e., the pathological urine formaldehyde concentration for AD is ˜1.4 times as much as the physiological concentration (9.61 ± 2.90 μM) in age-matched normal participants [24]. Accumulation of a pathological concentration of endogenous formaldehyde (15 μM) induced chronic damage to N2a cells [24,51], especially the impairment of neuronal processes and neurites, which may result from Tau hyperphosphorylation [51]. As described previously [52], the elevation of brain formaldehyde levels resulted from the administration of d -ribose may lead to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…慢性脱水损害认知功能, 继而又 使患者忘记饮水而加重脱水 [48] . 值得注意的是, 内源 甲 醛 浓 度 显著 低 于 饮 水剥 夺 组 [51] . 这 些 结 果 表明 , 按照《中国居民膳食营养素参考摄入量》所建议的饮 水量, 特别是在早晨醒来后饮水(成年男性350 mL, 成年女性300 mL), 可以显著降低甲醛在人体内的浓 度.…”
Section: 饮水频率均显著低于3月龄 且10月龄小鼠脑甲醛浓unclassified
“…It has been suggested that FA toxicity is related to the main hallmarks of age-related neuronal damage and Alzheimer's disease pathology (Tong et al, 2011 , 2013a , b , 2017 ; Liu et al, 2013 ). The elevated levels of FA found in Alzheimer's disease (Tang et al, 2013a , b ; Tong et al, 2013a , 2017 ) may play important roles in β-amyloid (Aβ) aggregation and cerebral amyloid angiopathy (Li et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%